New Understanding on the Pathophysiology and Treatment of Constipation in Parkinson’s Disease - Xu, Jianli; Wang, Lei; Chen, Xi; Le, Weidong (Frontiers in Aging Neuroscience, 2022)
Constipation, one of the most common prodromal non-motor symptoms of Parkinson's disease (PD), usually occurs several years earlier than the onset of motor symptoms. Previous studies have shown that constipation risk increases as the disease progresses. However, the mechanism underlying this pathologic disorder is not clear yet. Moreover, chronic constipation causes slowness in gastric emptying and therefore may lead to a delay in absorption of medications for PD, including levodopa and dopamine agonists. Accordingly, it is necessary to understand how the pathophysiological factors contribute to constipation during PD as well as pursue precise and effective treatment strategies. In this review, we encapsulate the molecular mechanism of constipation underlying PD and update the achievements in the treatments of PD-associated constipation.